Β‐arrestin2 recruitment at the β2 adrenergic receptor: A luciferase complementation assay adapted for undergraduate training in pharmacology. Issue 1 (28th January 2021) - Ferraiolo, Mattia; Beckers, Pauline; Marquet, Nicolas; Roumain, Martin; Ruiz, Lucie; Dupuis, Nadine; Hanson, Julien; Hermans, Emmanuel
Abstract: In the context of pharmacology teaching, hands‐on activities constitute an essential complement to theoretical lectures. Frequently, these activities consist in exposing fresh animal tissues or even living animals to selected drugs and qualitatively or quantitatively evaluating functional responses. However, technological advancements in pharmacological research and the growing concerns for animal experimentation support the need for innovative and flexible in vitro assays adapted for teaching purposes. We herein report the implementation of a luciferase complementation assay (LCA) enabling to dynamically monitor β‐arrestin2 recruitment at the β2 adrenergic receptor in the framework of pharmacological training at the faculty of Pharmacy and Biomedical Sciences. The assay allowed students to quantitatively characterize the competitive antagonism of propranolol, and to calculate pEC50, pKB, and pA2 values after a guided data analysis session. Moreover, the newly implemented workshop delivered highly reproducible results and were generally appreciated by students. As such, we report that the luciferase complementation‐based assay proved to be a straightforward, robust, and cost‐effective alternative to experiments performed on animal tissues, constituting a useful and flexible tool to enhance and update current hands‐on training in the context of pharmacological teaching. Abstract : The novel, animal‐free pharmacology workshop implemented at our faculty, combining in vitro experiments and data analysis sessions. It consists in a luciferase complementation assay (LCA) enabling to dynamically monitor β‐arrestin2 recruitment at the β2 adrenergic receptor. It allows students to characterize the competitive antagonism of propranolol by calculating pEC50, pKB, and pA2 values.